2017
DOI: 10.1186/s12883-017-0924-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of intracranial and extracranial artery stenosis in asymptomatic rural residents of 13 villages in China

Abstract: BackgroundThe present study aimed to investigate the prevalence and risk factors for extracranial carotid artery stenosis (ECAS) and intracranial carotid artery stenosis (ICAS) simultaneously in asymptomatic Chinese pure rural population.MethodsWe analyzed 2589 asymptomatic subjects aged over 30 yr. by ultrasonography and transcranial Doppler simultaneously in 13 isolated villages by door-to-door investigation. Both ECAS and ICAS were defined as more than 50% stenosis. Demographics, medical history documentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…The overall prevalence of aICAS (7.6%) amongst the rural-dwelling middle-aged and older adults was consistent with most previous studies in Asian populations [3,[8][9][10][11][12][13]. The Barcelona-AsIA study of a Caucasian Mediterranean population in Spain identified a prevalence of 8.6% for aICAS when TCD was used in combination with MRA to detect aICAS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall prevalence of aICAS (7.6%) amongst the rural-dwelling middle-aged and older adults was consistent with most previous studies in Asian populations [3,[8][9][10][11][12][13]. The Barcelona-AsIA study of a Caucasian Mediterranean population in Spain identified a prevalence of 8.6% for aICAS when TCD was used in combination with MRA to detect aICAS.…”
Section: Discussionsupporting
confidence: 88%
“…The Barcelona Asymptomatic Intracranial Atherosclerosis (Barcelona‐AsIA) study of Caucasians aged ≥50 years showed that the prevalence of any aICAS and moderate‐to‐severe aICAS was 8.6% and 3.3%, respectively . Several studies have reported that the prevalence of aICAS in Asian populations (aged ≥ 30 or 40 years) ranged from 4.7% to 15.7% . Most of these studies used either transcranial Doppler (TCD) or magnetic resonance angiography (MRA) to detect aICAS.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial stenosis may result in ischemic infarction (1) and is associated with a risk of ischemic stroke (2). Extracranial and intracranial carotid artery stenosis is common among symptomatic patients in China (3). Autopsy studies have proved that cerebral vascular occlusion is the major cause of stroke (4).…”
Section: Introductionmentioning
confidence: 99%
“…In later stages, plaques can mature and often become unstable, rupture, and lead to acute ischaemic events. It is reported that CAS events cause more deaths in developed countries than cancer and injuries, and with advances in health care and rising life expectancy, the prevalence of CAS in developing countries is still increasing [18][19][20]. Understanding and maxi mising primary prevention strategies for asymptomatic CAS is therefore critical.…”
Section: Discussionmentioning
confidence: 99%